Musykilatu at-Taraduf fi Tarjamati Riwayah Al-Hubb Daiman li Amil Muhamad Syata - Nur Fitriyani Hayati (Jurnal Internasional Pendidikan Bahasa Arab, 2019)
This research discusses the translation problems of synonymous words in the Arabic novel Al-Hubb Daiman. This novel written by Amil Muhamad Syata, consists of ten episodes and published in 2009 by خوارزم العلمية للنشر والتوزيع Jeddah. In addition to the story, this novel also mentions several events and situations in the city of Mecca and the surrounding area, its food, culture and so on. So, this novel is interesting to be translated into Indonesian. After the researcher translated the entire text of the novel into Indonesian. One of the problems that faced by the author in translating the novel Al-Hubb Daiman the translation of several words that are synonymous. Literally the word synonym is another name for the same thing. Synonym is a phrase which is more or less the same meaning as another expression. The research results that there are three ways to translate synonymous words: 1). Two words that are synonymous translated with one word. The words that are synonymous in this initial step the author found as many as 33 words, 2.) Reduce the words that are synonymous. In this second step synonyms are found as many as 7, and 3). Two words that are synonymous with both. In this step the writer found 8 words. The total number of words synonymous in the Al-Hubb Daiman novel that the author found was 48 words.